The Reclamation of Sami identity and the traces of Swedish colonialism : A qualitative study about the formation of Saminess and Sami identity - Frida Olofsson (2020)
Dat åtsådibme guoradálla gåk Samievuohta ja sámeidentitähtta habbmituvva gå tjalmostahtta gåk sámevuohta manna buolvas buolvaj. Giehtja gatjádallama li dahkatum ulmutjij gejna’l sámeduohke ja guoradallam tjato dej tebmaj ma vuojnujin gatjádallamijn. Da tebma lidjin: Sirddet sámeárbbev buolvas buolvaj, sámeidentitähtta, gåk vuosset sån la sáme ja sáme attribuhtta. Teoriddja ma adnejuvvujin lidjin postkoloniala teoridja ja identitähttateoridja. Materiálla vuosidin ajn dat svieriga kolonialisma bajna konstruksjåvvnåv sámeidentitähttaj. Sihtat valdit ruptus sámeidentitähttav, arbbev ja gulluvasjvuohtav la garras hållin da guthi oassálasstin. Dav mahta javllat la ájnas lávkke váldet ruopptot mij la dåssjåm gájkka sameálmmukkies The purpose of this study was to study identity formation among Sami people. The aim was therefore to investigate how Saminess and Sami identity is formed and specifically the way the Sami community transfers the identity. Semi structured interviews were conducted and the material was analyzed by the use of a thematic analysis. In the analysis of the material, four main themes were : Transfer of Sami heritage over generations, Sami identity, Expressions about being Sami and Sami attributes. The theoretical framework consisted of Postcolonial theory and theoretical concepts of identity. The main findings showed that the traces of colonialism is still present in the identity-formation of the Sami people and that there is a strong silence-culture related to the experiences of colonial events which consequently also have affected the intergenerational transfer of Saminess and Sami identity. Furthermore, the will to reclaim the Sami identity, heritage and the importance of a sense of belonging is strongly expressed by the participants. This can in turn be seen as a crucial step for the decolonization process of the Sami population as a whole.